Choosing Wisely: Computed Tomography in the Diagnosis of Adolescents With Intrathoracic Tuberculosis. (27th November 2020) - Kakalia, Spenta; Chakravarty, Aparna; Manson, David; Lam, Ray; Waters, Valerie; Kitai, Ian
Abstract: In a retrospective study of adolescents with intrathoracic tuberculosis (TB), 26 out of the 81 (32%) patients had undergone chest computed tomography (CT). Chest CT was considered unnecessary in 7 (27%), necessary in 7 (27%), and possibly/probably helpful in 12 (46%). Promptly obtaining specimens for sputum smear microscopy, molecular testing, as well as culture for Mycobacterium tuberculosis could avoid several unnecessary CTs.